CORPORA AND TEACHING ENGLISH AS A FOREIGN LANGUAGE - MOHAMED GRAZIB (My University, 2008)
This research investigates the uses of corpora in teaching English as a foreign language. It shows also the uses of corpora in the different applied linguistic domains and after the focus will be upon the pedagogical domain. Nowadays, technology has emerged almost all the domains in our daily life, the existence of such facilities (computers, internet, and corpora) could be of paramount advantages in the teaching domains. Students are changing, behaviours are changing, mentalities are also changing, and thus it is time to change the teaching methods and to incorporate the best that technology offers. This research deals with all the approaches and methods used over the world, but the common thing in all these approaches is that the corpus is in the centre of our interest. Some solutions have been presented to teachers in the case where computers won’t be available. Some examples show and explain how to practice corpora without computers. This research is only an attempt to popularise the elementary uses of corpora in teaching English as a foreign language in Algeria. We hope that this experience will know the expected success it has recently knew in many countries.